2019
DOI: 10.1038/s41598-019-46965-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment, and Control of Hypertension in Korea

Abstract: The purpose of the present study was to describe the temporal trends in prevalence and management status of hypertension in Korea between 1998 and 2015. Data of adults who were aged 30 years or older were extracted from the Korea National Health and Nutrition Examination Survey, a nationwide representative population-based survey. Hypertension was prevalent in 30.5% of Korean adults. The age and sex standardized prevalence showed little change between 1998 and 2015. The elderly population and men showed higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
2
64
1
Order By: Relevance
“…The move toward intensive BP control is also similar in the U.S. and in Europe [5,17]. Previous studies have shown hypertension awareness, treatment, and control rates increased remarkably until 2007, but showed a plateau thereafter [12,18]. The present study also suggests that there is room for improvement in BP control among Korean adults with hypertension.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The move toward intensive BP control is also similar in the U.S. and in Europe [5,17]. Previous studies have shown hypertension awareness, treatment, and control rates increased remarkably until 2007, but showed a plateau thereafter [12,18]. The present study also suggests that there is room for improvement in BP control among Korean adults with hypertension.…”
Section: Discussionsupporting
confidence: 77%
“…The 2018 KSH guidelines maintained its BP criteria for hypertension (systolic BP ≥140 mmHg or diastolic BP ≥90 mmHg) [8]. There were only small changes in the ranges of elevated BP and prehypertension [12]. The 2017 ACC/AHA hypertension guidelines lowered the threshold for hypertension from 140/90 mmHg to 130/ 80 mmHg [13].…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured three times on the subject’s right arm using an appropriately sized arm cuff and mercury sphygmomanometer (Baumanometer; WA Baum Co., New York, NY, USA). It was measured in a seated position for at least 5 min and the final BP was the mean value of the second and third measurements [ 37 ]. Hypertension was defined as a systolic blood pressure (SBP) ≥140 mmHg or a diastolic blood pressure (DBP) ≥90 mmHg, or use of anti-hypertensive medications, or diagnosis from a doctor.…”
Section: Methodsmentioning
confidence: 99%
“…In Korea 29 , a 2019 report revealed that the prevalence, awareness, treatment, and control of hypertension in adults aged 30 years or older was 30.5%, 67.3%, 63.6%, and 46.2%, respectively. However, in our study in Inner Mongolia, the control rate of hypertension was only 8.6%.…”
Section: Discussionmentioning
confidence: 99%